2013
DOI: 10.1186/1471-2458-13-553
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic disparity in cervical cancer screening among Korean women: 1998–2010

Abstract: Background: Cervical cancer is the sixth most common cause of cancer among Korean women and is one of the most preventable cancers in the world. This study aimed to investigate the change in cervical cancer screening rates, the level of socioeconomic disparities in cervical cancer screening participation, and whether there was a reduction in these disparities between 1998 and 2010. Methods: Using the Korean Health and Nutrition Examination Survey, women 30 years or older without a history of cervical cancer an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 27 publications
(22 reference statements)
1
20
1
Order By: Relevance
“…In the present study, fewer than half of Chinese older women had ever had a test, a lower rate than those reported by the comparable age group in other populations [16,17,19,20,21]. The majority of these women (65%) perceived their own low susceptibility to cancer, and 30% were unsure about their risk.…”
Section: Discussioncontrasting
confidence: 78%
“…In the present study, fewer than half of Chinese older women had ever had a test, a lower rate than those reported by the comparable age group in other populations [16,17,19,20,21]. The majority of these women (65%) perceived their own low susceptibility to cancer, and 30% were unsure about their risk.…”
Section: Discussioncontrasting
confidence: 78%
“…In contrast, women of lower socioeconomic status and education, unemployed and disabled women, and women who do not have a habit of visiting a gynecologist regularly are less likely to enter a screening program [25]. Some previous studies in the field have shown that household income is a significant predictor of cervical cancer screening practices and habits [26]. The current findings from Latin America show that the knowledge about the Pap smears and their importance in cancer prevention increases with age (reaching a plateau in the age group 31-35 years) and with education levels.…”
Section: Discussionmentioning
confidence: 99%
“…The current literature suggests that participation in cervical screenings of those individuals with lower income can be enhanced with adequate interventions at the primary health care level, where an additional focus should be placed on the members of vulnerable groups. Therefore, it is important to keep monitoring how the current public health policies, like expanding the scope of free cervical cancer examination of women whose households are in the lower 50% of the income bracket, impact the participation rates over time [26].…”
Section: Discussionmentioning
confidence: 99%
“…showed that insurance status is an independent predictor for poorer survival outcome, as it is related to late‐stage presentation and under‐treatment in the USA. Low socio‐economic and educational status are important factors, as compliance with cancer screening is significantly lower in this population, even in the UK, where screening is free to all irrespective of insurance status . Reasons for non‐compliance when access and finance are not an issue could be a lack of understanding of the natural history of cervical cancer and the role of screening, or because patient focus is more on prominent daily life issues and concerns rather than attending smear test invitations.…”
Section: Discussionmentioning
confidence: 99%
“…Low socio-economic and educational status are important factors, as compliance with cancer screening is significantly lower in this population, even in the UK, where screening is free to all irrespective of insurance status. 22,23 Reasons for non-compliance when access and finance are not an issue could be a lack of understanding of the natural history of cervical cancer and the role of screening, or because patient focus is more on prominent daily life issues and concerns rather than attending smear test invitations. Practical barriers were raised more often by younger women, whereas older women had more negative attitudes to screening.…”
Section: Discussionmentioning
confidence: 99%